Once Again About Balts, Gudai, Goths and Their Origins - Butkus, Alvydas; Lanza, Stefano M. (Respectus Philologicus, 2012)
This paper aims to shed light on the tenacious tendency of would-be philologists and self-taught historians to embellish the history of the Lithuanian nation and its civilization by providing interpretations of ancient texts without real evidence. In particular, the authors review some methodological aspects of historical research in the work of the Lithuanian émigré J. Statkutė de Rosales, Europos šaknys ir mes, lietuviai (The Roots of Europe and We, the Lithuanians). This article points out that her claim that the Goths were the mighty ancestors of today’s Lithuanians derives from a macroscopic misinterpretation and alteration of the only existing text about the origin of the Goths, which is the late Latin Getica, written by Jordanes. Statkutė, who recently received a doctorate honoris causa, identifies the Goths with the ancient Lithuanians by comparing the word Gothi with the Lithuanian ethnonym gudai, and asserts that world historians have intentionally been duped for years by a few deceitful scholars into believing that the Goths originated in Scandinavia. Statkutė holds that the island of Scandza depicted by Jordanes should not be identified with Scandinavia at all, but with the Baltic coast from Eastern Poland to Lithuania.The authors of this paper examine the actual text of Jordanes both philologically and with cross-references to other authors, finding that Statkutė’s conclusions are extremely erroneous. Not only has the Latin text been incorrectly translated by Statkutė in more than one passage, but she has also kept silent – most probably on purpose – about some crucial information, thereby lending support to her theories. The identification of Scandza, the fatherland of the Goths according to Jordanes, with the Baltic coast has to be ruled out mainly by the fact that the Latin historian clearly describes the phenomena of the polar night and midnight sun as being typical of Northern Scandza. Statkutė’s approach to sources written in Latin also appears compromised, not only by leaving out relevant information, but also by her difficulty in understanding (and therefore translating) the texts as well. The authors of this paper point out several other misinterpretations of facts, which are presented in her book as more or less revolutionary findings. In addition, Statkutė’s arrogant accusations against distinguished scholars would be inappropriate even if she were correct in her assumptions. As a matter of fact, her sole merit today is the attempt to arouse Lithuanians’ interest in their own distant past.
Keywords: Goths; Scandinavia; Statkutė de Rosales; Jordanes; Praetorius; pseudotheories